High Blood Pressure during Pregnancy is not a Protective Factor for Preterm Infants with Very Low Birth Weight. A Case-Control Study - Annibal Tagliaferri Sabino; Eduardo de Souza; Ana Lucia Goulart; Adriana Martins de Lima; Nelson Sass (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Objective To evaluate whether the presence of maternal blood pressure reduces the risks of morbidity, perinatal mortality and morbidity at 24 months of age in very low birth weight infants (VLBWIs) compared with a control group. Methods A retrospective, observational, case-control study. Total 49 VLBWIs were allocated to the study group, called the maternal arterial hypertension group (AHG), and matched with 44 in the control group (CG). The infants were assessed during hospitalization and at 12 and 24 months corrected age at a specialized clinic. For the assessment of growth, the World Health Organization (WHO) Anthro software (Geneva, 2006) was used, and for the psychomotor assessment, the Denver II test was used. Results In relation to the antenatal variables, the infants of the AHG had more centralized circulation assessed by Doppler, received more corticosteroids and magnesium sulfate, and were born by cesarean section more frequently. In terms of the postnatal and in-hospital outcomes, the AHG had a higher gestational age at birth (30.7 versus 29.6 weeks) and a lower frequency of 5-minute Apgar scores of less than 7 (26.5% versus 52.3%). The CG had a higher rate of pulmonary dysplasia (30.2% versus 8.3%). There were no differences in terms of hospital mortality, complications, somatic growth and functional problems at 24 months of corrected age. Conclusion The presence of maternal hypertension, especially preeclampsia, was not a protective factor against morbidity, mortality and evolution in VLBWIs aged up to 24 months. Therefore, the clinical practice should be focused on prolonging the pregnancy for as long as possible in these conditions as well.